2022
DOI: 10.3389/fphar.2022.944540
|View full text |Cite
|
Sign up to set email alerts
|

Changing Characteristics of Pharmaceutical Prices in China Under Centralized Procurement Policy: A Multi-Intervention Interrupted Time Series

Abstract: Objective: National centralized drug procurement organized by the Chinese government currently represents the largest group purchasing organization worldwide, to establish a reasonable price formation mechanism. This study aimed to evaluate the effects of centralized procurement policy on drug price and price ratio in China.Method: Monthly drug procurement data of public medical institutions were extracted from the national procurement database, including 11 pilot cities and 36 months from January 2018 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…We believe that both drug national negotiation and volume-based procurement are only transient policy effects, although they can significantly reduce prices in the current period, they do not exert sustained downward policy pressure on drug prices (basically do not affect the trend of price changes) ( 30 , 31 ). After the point in time of drug national negotiation and volume-based procurement, competition is still the main factor that makes prices lower.…”
Section: Methodsmentioning
confidence: 98%
“…We believe that both drug national negotiation and volume-based procurement are only transient policy effects, although they can significantly reduce prices in the current period, they do not exert sustained downward policy pressure on drug prices (basically do not affect the trend of price changes) ( 30 , 31 ). After the point in time of drug national negotiation and volume-based procurement, competition is still the main factor that makes prices lower.…”
Section: Methodsmentioning
confidence: 98%
“…In order to control for potential confounding variables, ensure the accuracy and reliability of causal inferences, and thus reduce bias in the estimation of causal effects and improve internal validity, we introduced corresponding control variables. Based on the variables used in previous studies [14,26,36,[38][39][40][41], we selected several internal and external control variables to control the regression of the model and conducted a rigorous causality analysis in the inclusion of covariates in accordance with the ndings of a previous study [43]. Among the internal control variables, operating costs, compensation payable to employees, and the number of employees are mainly used to determine the costs of the enterprise,…”
Section: Wherementioning
confidence: 99%
“…2016 ). Hongfei observed that purchasing by the Chinese government organization led to marked price reductions in the labeled medicines, but the price distribution was too diffuse and the price ratios were not reasonable, requiring further and effective price regulation means ( Long et al, 2022 ).…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%